Study of Testosterone Levels in type-II Diabetes Mellitus Patients in North Karnataka Population: Editor's Note: This article has been retracted as of January 2026 as it is out of scope (Indian Journal of Public Health Research & Development, 2023)
Background: Type-II DM is a major health problem globally. There are various complications related to diabetes mellitus, among them low testosterone levels in men is very obvious, health problem which affects the reproduction and sexual life.Method: 250 type-II DM patients at different age groups were studied and compared with 150 controlled groups.The clinical investigation included- FBS, PPBS, Blood urea, S. creatinine, HBA1C, lipid profile, Urine for albumin creatinine ratio, S. testosterone was estimated by using chemiluminescence immune assay and HbA1c by HPLC.Results: BMI in type-II DM group was 25.83 (±2.33) and controlled group was 24.8 (±3.22). Mean HBA1C in type-II DM group was 8.81 (±1.93) and 4.80 (±0.402) in controlled group. S. testosterone level was 119.11 (±86.45) in type-II DM group and 402 (± 171.52) in controlled group.Conclusion: This study revealed that higher sugar level is inversely proportion to lower testosterone levels. It will be a guide to physician, endocrinologist to treat such patients efficiently to elevate the testosterone levels
Keywords: Chemiluminescence immune assay, HPLC, HbA1C, Metabolic syndrome.